Sistem Pakar Diagnosa Kerusakan Mobil Avanza Dengan Metode Certainty Factor Menggunakan Bahasa Pemrograman PhP Dan Database MySQL - Edo Cahyadi; Radiyan Rahim (Riset Sinergi Indonesia (RISINDO), 2025)
The development of automotive technology has led to increased vehicle system complexity, creating the need for intelligent solutions to assist in fault diagnosis. One of the common problems faced by Avanza car users is the difficulty in detecting engine damage at an early stage. Therefore, this study aims to develop an expert system capable of diagnosing Avanza car malfunctions using the Certainty Factor method in a web-based environment. The system was developed using PHP as the programming language and MySQL as the database to manage symptoms, malfunction data, and certainty values for each diagnosis. The Certainty Factor method was implemented to calculate the level of confidence in potential malfunctions based on user-inputted symptoms. The results indicate that the method provides accurate diagnostic outcomes by presenting certainty values for each possible malfunction. This expert system helps both technicians and users obtain preliminary information about the vehicle’s condition before performing direct inspections at the workshop. Therefore, the developed expert system improves efficiency, accuracy, and service quality in diagnosing Avanza car malfunctions.